Gender diversity at workplace: Its implications on organizational performance at IT sector in Hyderabad - Pulusumamidi Neelima; Betgeri Sai Nethra; Parameshwari Chekuri Naga (MATEC Web of Conferences, 2024)
The intellect and awareness of humans are thought to set them apart from one another. Studies conducted over the last few decades have demonstrated that women represent a substantial untapped reservoir of human capital. A growing number of competent women are entering fields that were previously thought to be exclusively male, thanks to the development of information technology and improved educational facilities. Because it is so important for businesses to draw in and keep workers in this fiercely competitive market, senior management has been paying enough attention to the creation of a women-friendly workplace. The bulk of research indicates that encouraging gender diversity has a beneficial impact on creativity and innovation. As a result, modern IT companies in India are implementing policies that guarantee a diverse workplace that is friendly to female employees. The aim of this paper is to examine the correlation between workplace assent of gender diversity, IT industry activities, and barriers to their implementation.